Linguistic semantics and lexicography: A troubled relationship - Lew, Robert (Peter Lang, 2007)
The paper addresses the issue of the relationship between lexicography linguistic semantics, arguing that lexicography should be seen as a separate discipline.
Keywords: Lexicography; Linguistics; Semantics